A multi-study analysis enables identification of potential microbial features associated with skin aging signs - Myers, Tyler; Bouslimani, Amina; Huang, Shi; Hansen, Shalisa T.; Clavaud, Cécile; Azouaoui, Anissa; Ott, Alban; Gueniche, Audrey; Bouez, Charbel; Zheng, Qian; Aguilar, Luc; Knight, Rob; et al. (Frontiers in Aging, 2024)
We confirm the positive link between chronological age and skin microbiome diversity, but we also observed a global positive association between microbiome diversity and grade of Crow's feet wrinkles, one of the key signs of skin aging, although the relationship varied among the included sub-studies. We additionally observed a negative link between microbiome diversity and transepidermal water loss.• The link between Crow's feet wrinkles and microbial features were explored while considering the effect of individual studies and chronological age as a confounder, identifying several potential biomarkers.• Building a multi-study analysis using independent studies is a valuable method to bolster sample sizes and address questions not possible by individual studies alone. However, as the sub-studies are often generated by different principal investigators and methods, analysis relies on data harmonization and the use of analytic tools that are able to account for those differences.